Fleas and Ticks in Carnivores From a Domestic–Wildlife Interface: Implications for Public Health and Wildlife. Issue 6 (18th August 2016) - Poo-Muñoz, Daniela A.; Elizondo-Patrone, Claudia; Escobar, Luis E.; Astorga, Francisca; Bermúdez, Sergio E.; Martínez-Valdebenito, Constanza; Abarca, Katia; Medina-Vogel, Gonzalo
Abstract: Fleas and ticks are parasites of wild and domestic mammals, and can be vectors of several pathogens. In rural areas, domestic carnivores such as the domestic dog ( Canis lupus familiaris L.), may act as a "bridge" between natural areas and human settlements where ectoparasites can be used as a metric of such link. The aim of this study was to identify fleas, ticks, and Rickettsia spp., collected from domestic and wild carnivores in a natural reserve and surrounding human settlements in Central Chile, using morphological keys and molecular analysis. We surveyed 170 households from which 107 dogs and eight cats were sampled. From the natural reserve, we sampled two chilla foxes ( Pseudalopex griseus Gray), two lesser grison ( Galictis cuja Molina), three kodkods ( Leopardus guigna Molina), and four dogs. From dogs, we collected Ctenocephalides felis Bouché, Ctenocephalides canis Curtis, Pulex irritans L., and Rhipicephalus sanguineus s.l. Latreille; C. felis was the most frequent ectoparasite. Cats were infested only by C. felis and Rh. sanguineus s.l. From wild carnivores, we obtained C. canis and P. irritans, the latter being most frequent. Molecular analysis of P. irritans detected 10 haplotypes and two main clades, which tended to separate fleas from wild and domestic hosts. Molecular analysis of omp A and omp B genes confirmed the presence of Rickettsia felis in fleas collected from owned dogs and cats, which could represent a potential risk factor of R. felis transmission in the area.